Analisis Pelaksanaan Penyusunan Administrasi Kepenghuluan di Kementerian Agama Kabupaten Ogan Ilir - Iswardi, Iswardi; Syuroh, Mat; Febrianza, Muhammad (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
In the Regulation of the Director General of Islamic Guidance No. DJ.II/426 of 2008 concerning Guidelines for the Implementation of Duties and Credit Score Assessment for the Functional Position of